Penerapan Strategi Pembelajaran Everyone Is Teacher Here Untuk Meningkatkan Keterampilan Berbicara Siswa - Lilis Nurmalasari (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research motivated by the low results of students speaking skills. This study aims to find out the results of students speaking skills before using the strategy everyone is teacher, the learning process using strategy everyone is teacher here, also to find out the results of students speaking skills after using the strategy everyone is teacher here on Indonesian language subjects in class V MI Al Musdariyah District Cileunyi Regency Bandung. The Method used is a classroom action research method.The data collection technique uses observation for work and documentation. Data analysis uses the observation sheet and performance. The study subjects consisted of 24 students, 10 women and 14 men. The results of the data analysis concluded that (1) The students speaking skills before using the strategy everyone is teacher here is still low with an average value of 46,9. (2) Implementation of the strategy everyone is teacher here goes well according to the stages. Teacher and student activities have increased in each cycle. (3) Students speaking skills after using the strategy everyone is teacher here has increased every silk cycle. The percentage of classical learning completeness in pre cycle 8,3%, cycle I is 41,5%, and cycle II is 91%.